Self-Transcendent Aspirations and Life Satisfaction: The Moderated Mediation Role of Gratitude Considering Conditional Effects of Affective and Cognitive Empathy - Oriol, Xavier; Unanue, Jesús; Miranda, Rafael; Amutio, Alberto; Bazán, César (Frontiers in Psychology, 2020)
Life aspirations are considered one of the most relevant components for human beings to give meaning and purpose to their existence. Different studies emphasized the relevance of intrinsic life aspirations to promote life satisfaction. However, few studies analyze the specific role of the intrinsic aspirations that have been recently categorized as self-transcendent. Self-transcendent aspirations are focused on helping others and improving society and consequently are considered aspirations whose purpose transcends oneself. In this sense, the objective of this study is to observe how self-transcendent aspirations are related to life satisfaction through dispositional gratitude. Additionally, we aim to study the moderating role of cognitive and affective empathy. 1,356 students (M=21.5; SD=2.35) took part in a scholarship program funded by the Education Ministry of Peru (PRONABEC), of which, 57.7% were men and 42.3% were women. Results show a strong relationship between self-transcendent aspirations, gratitude, and cognitive and affective empathy. In the mediation analysis, an indirect effect of self-transcendent aspirations is observed on life satisfaction via gratitude. However, the moderated mediation showed that the addition of cognitive and affective empathy conditions the mediation effect. In this way, cognitive empathy has a significant interaction in the relationships between self-transcendent aspirations and gratitude, and between self-transcendent aspirations and life satisfaction. Results are discussed to emphasize the relevance of the mediating and moderating mechanisms considered in this study for the understanding of how self-transcendent life aspirations may promote life satisfaction.